Self-worth Pada Individu Dengan Body Dysmorphic Disorder yang Menjalani Bedah Kosmetik - Janice Valencia; Atika Amalia Dewi (Philanthropy: Journal of Psychology, 2021)
Body dysmorphic disorder (BDD) is a psychiatry disorder related to body image. Individuals with BDD are found to have low self-worth, this is the cause of individuals with BDD to have cosmetic surgery. The purpose of this article is to determine the relationship of self-worth in individuals with BDD in performing cosmetic surgery. In this systematic review, there were 20 articles that met the criteria, there were 12 articles with the variable self-worth with BDD, 4 articles with the variable self-worth, BDD, and cosmetic surgery, and 4 articles with the variable BDD and cosmetic surgery. Based on the results of a systematic review, it was found that individuals with BDD have low self-worth, this low self-worth makes individuals with BDD perform cosmetic surgery.